Simulation of CZTSSe single solar cells by AFORS-HET software - Buthina M. Jandary; Ayed N. Saleh (Tikrit Journal of Pure Science, 2020)
In this paper, this sthdy simulated photovoltaic characteristics of single heterojunction solar cell with Cu2ZnSnS4 and Cu2ZnSnSe4 absorber layer numerically using the AFORS-HET program .n-CdS/ZnO double buffer layer is used for hetrostructure interfaces with the absorber layer. The cell performance is investigated against variation of different absorption layer properties such as thickness, carrier concentration. The mixed zinc and cadmium sulphide (Cd1-X Zn X S) is hired as buffer layers and reseach of the effect  its thickness. CdS was selected a buffer because it improves the interface with absorbent CZTSSe and has a lofty  sending  in the blue wavelength. at thickness =1 μm and acceptor concentration (Na=7.9×1015 cm-3) ,a maximum efficiency  (η=11.9%)  is provided  with an open-circuit voltage (Voc=688mv), short-circuit current (Jsc=24.6 mA.cm-2) and fill factor (FF =70.8 of the CZTS solar cell, and Voc=(597 mv), Jsc= (41.7mA.cm-2), FF = (81.2 %) and η= (20.2%) of the CZTSe solar cell.